Evaluación de la aplicación del método fenton a nivel laboratorio en la planta de tratamiento de aguas residuales de la empresa Aguas San Juan S.A.S. ESP (2016)
Aguas San Juan ESP is dedicated to wastewater treatment from different processes. Water discharges benefit, are characterized by the high content of organic and inorganic matter, including fats, chlorides, suspended solids, are surface-active. Wastewater characterization was performed for this sample of dumping of the poultry and livestock industry was taken. For the beginning of this stage, a pre-experiment where operating conditions were evaluated and determined variables was performed. The method was performed in Fenton operating conditions at a pH range from 2.7 to 3.1, temperature of 20 ° C, with which the COD / H2O2 and H2O2 / Fe + 2 ratios for each experiment was determined.